Крисп - Лангадасская, Литийская и Рентинская митрополия - Алексий (2015)
Экземпляры: чит. зал (28.11.16.) / Инвентарный номер: 2540 / Цена: / Сис.шифр: 86.372 я2 / Авт.знак: П 68 / ГРНТИ: 21.15.69 / ББК: 86.372я2